Coassembly of a new insect cuticular protein and chitosan via liquid–liquid phase separation - Gong, Qiuyu (2022)
Insect cuticle is a fiber-reinforced composite material that consists of polysaccharide chitin fibers and a protein matrix. The molecular interactions between insect cuticle proteins and chitin that govern the assembly and evolution of cuticle are still not well understood. Herein, we report that Ostrinia furnacalis cuticular protein hypothetical-1 (OfCPH-1), a newly discovered and most abundant cuticular protein from Asian corn borer Ostrinia furnacalis, can form coacervates in the presence of chitosan. The OfCPH-1-chitosan coacervate micro-droplets are initially liquid-like, but become gel-like with increasing time or salt concentration. The liquid-to-gel transition is driven by hydrogen-bonding interactions, during which an induced β-sheet structure of OfCPH-1 is observed. Given the abundance of OfCPH-1 in the cuticle of Ostrinia furnacalis, this liquid-liquid phase separation process and its aging behavior could play critical roles in the formation of the cuticle.